Becoming an excellent teaching practitioner: A study of assessment design in a higher education institution - Gynnild, Vidar; Gynnild, Astrid (Journal of Praxis in Higher Education, 2025)
In higher education worldwide, the terms ‘teaching excellence’ and ‘educational merit systems’ are frequently used in institutional policy documents. Following international assessment trends, Nordic universities and colleges have for decades encouraged educators to apply for the Excellent Teaching Practitioner (ETP) award. However, little is known about rejected applicants’ experiences with such assessment processes, and how such knowledge could contribute to further quality improvement. This thematic analysis of an ETP process at a large Nordic higher education institution shows that social–psychological effects of such processes ought to be investigated more closely. This study indicates that applicants were shocked and distressed by the discursive opaqueness and a lack of alignment in the assessment design. Administrative maneuvers to standardize the assessment design came into conflict with academically established evaluation principles such as transparency, authenticity, validity, reliability, and fairness.